Hubungan antara Iklim Organisasi dengan Work Family Balance pada Guru Wanita Bersertifikasi yang Sudah Berkeluarga - Diana Trie Yunisa; Herio Rizki Dewinda (Psyche 165 Journal, 2020)
The research purpose to determine the relationship between organizational climate and work family balance in certified teachers in married women in SMP N 2 Sawahlunto. The independent variable in this research is organizational climate and the dependent variable is work family balance. The sampling tecnique in this research use saturated sampling technique. The sample in this study were 33 certified teacher in married women in SMP N 2 Sawahlunto. The validity and reliability test in this study uses the alpha cronbach technique. The result of the validity coefficien on the scale of organizational climate moves from rix= 0.326 to rix= 0.742 with a reliability coefficient of α = 0.915 while on the work family balance move from rix = 0.304 to rix = 0.726 with a reliability coefficient of α = 0.904. Based on data analysis, a correlation value of 0.671 that is with a significance level of 0.000, which means the hypothesis is accepted. This shows that there is a significant relationship organizational climate and work family balance in certified teachers in married women in SMP N 2 Sawahlunto. The effective contribution of the organizational climate variable to work family balance 45%